Pendampingan Pembuatan Konten Marketing Pada UMKM Di Desa Suka Jaya Kabupaten Bungo - Nanik Istianingsih; Susriyanti Susriyanti; Ariyanto M; Muhammad Nasir; Delvita Juniarsih (CV. Aksara Global Akademia, 2026)
Advancements in digital technology are compelling Micro, Small, and Medium Enterprises (MSMEs) to adapt by adopting social media-based marketing strategies. Instagram stands out as a highly promising promotional platform due to its visual and interactive nature, as well as its ability to reach a vast audience. However, many MSMEs still lack the knowledge and skills required to produce effective digital content. This Community Service (PKM) initiative aims to enhance MSME capabilities in creating Instagram-based digital content for business promotion. The program was implemented through a process of identifying partner challenges, providing training, facilitating hands-on practice, and offering ongoing mentorship. The results demonstrate improved understanding and proficiency among MSME partners in managing business Instagram accounts, creating innovative promotional content, and boosting digital promotional activity and engagement. The initiative also fostered a shift in mindset among MSMEs, moving them from traditional marketing toward more flexible and sustainable digital marketing practices. Ultimately, the guidance provided for Instagram content creation successfully bolstered the competitiveness of MSMEs in the digital era.